The Impact of Digital Literacy on Children’s Academic Performance - Ethan Jian; Ryan Wei Sheng (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2023)
As digital technology becomes more integrated into the classroom, digital literacy is increasingly seen as essential for academic success. This paper examines the relationship between digital literacy and children's academic performance. It reviews how digital literacy skills—such as information retrieval, critical thinking, and digital communication—affect students' learning outcomes in various subjects. The findings suggest that a high level of digital literacy positively influences children's ability to perform academically and adapt to digital learning environments.